2014
DOI: 10.1155/2014/845142
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Tree Diversity and Stand Structure during Restoration: A Case Study in Fragmented Moist Deciduous Forest Ecosystems of Northeast India

Abstract: Ecological implications for the conservation of fragmented forests to managed local plant diversity have recently drawn much attention of most conservationists. Present study investigates the importance of fragmented forests using different quantitative measures of species diversity and stand structure as indicators of natural restoration from past disturbances. Eleven independent 500 m × 10 m belt transects (5.5 ha) were established within fragmented low land moist deciduous forests of Tripura. All woody plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The proportion of individuals in the lower diameter class (5-15cm dbh) was high in the disturbed sites. Recruitment of light tolerant species might have increased the stem density of the stand following disturbance (Majumdar et al, 2014). The low density in Very Large category may be due to thinning effect caused by larger trees as reported from the sholas of Western Ghats (Mohandass and Davidar, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The proportion of individuals in the lower diameter class (5-15cm dbh) was high in the disturbed sites. Recruitment of light tolerant species might have increased the stem density of the stand following disturbance (Majumdar et al, 2014). The low density in Very Large category may be due to thinning effect caused by larger trees as reported from the sholas of Western Ghats (Mohandass and Davidar, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…However, Wild Boar, Barking Deer, Palm Civet, Wild Cat, Jackal, Indian Giant Squarrel, Wild Dog, and many species of birds and herpato-faunal species are concentrated in the interior zone (Gupta et al 2004). As per the classification system proposed by Champion and Seth (1968) and revised by Majumdar et al (2014) the main vegetation types of this sanctuary shows similar characteristics to Moist Mixed Deciduous Forest (3C/C3), East Himalayan Lower Bhabar Sal (3C/C1b (ii)), Moist Bamboo Brakes (2B/E3) and fragmented patches of Cachar Tropical Semi Evergreen Forest (2B/2s2/c2). Early 1980s, pure Dipterocarpus turbinatus or sometime mixed with Shorea robusta were predominantly distributed within in Kashari RF (Reserved Forest) and Trishna PRF (Protected Reserved Forest), which constituted the main reserve area of Trishna Wildlife sanctuary.…”
Section: Study Areamentioning
confidence: 67%
“…Each line transects encompassed five 10 m 9 100 m contiguous sub-plots (5 9 0.1 ha), thus 35 sub-plots (3.5 ha) were laid in the interior zone, 35 subplots (3.5 ha) plots in the marginal forest surrounding the interior forest and 30 sub-plots (3 ha) were laid outside the interior habitat close to human settlements. All the individual stem C10 cm gbh (girth at breast height) were measured in centimeter at 1.36 m height and height of each species were measured in nearest meters in living and nonliving categories (Majumdar et al 2014). All species encountered within the sampling plots that attained at C10 cm gbh were documented in the datasheets.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, some trees are kept inside or in the boarding the plantation for shade, fencing and timber requirements. A recent study found that diversity and density of trees in rubber plantation including its marginal forest fragments were low compared to other semi-natural plantation and natural vegetation 29,31 . The common species ofthe ground vegetation of rubber plantation include Altenthera sp., Cleodendrum viscosum, Pavetaindica, Spilanthuspaniculata, Desmodium sp., Blumiasp, Agiratumconyzoides, Spermacoseaehispida, Rungiapectinata, Momosapudica, Eupatorium odoratum etc.…”
Section: Effect Of Rubber On Soilmentioning
confidence: 98%